2015
DOI: 10.1177/1049732315578402
|View full text |Cite
|
Sign up to set email alerts
|

Shame and Gender Differences in Paths to Youth Suicide

Abstract: Risk factors, suicidal behavior, and help-seeking patterns differ between young women and men. We constructed a generic conceptual model of the processes underlying youth suicide, grounded in 78 interviews with parents in 52 consecutive cases of suicide (19 women, 33 men) identified at forensic medical autopsy and compared by sex. We found different forms of shame hidden behind gender-specific masks, as well as gender differences in their paths to suicide. Several interacting factors formed negative feedback l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Most participants reported that, over time, they had learned to make sense of selfharm and to understand why young people had self-harmed. Many of the reasons they identified are reported in the research literature as factors which are known to contribute to self-harm, including: psychiatric and personality disorders (Hawton, Saunders, Topiwala & Haw, 2013); psychological characteristics such as impulsivity and low self-esteem (Madge et al 2011); stressful life events such as difficulties in relationships, knowing someone else who self-harms or who has attempted suicide, being sexually abused or being bullied (Madge et al 2011;Werbart Törnblom, Werbart & Rydelius, 2015). A high level of impulsivity in early childhood has been implicated in later adolescent self-harming (Goldston, Daniel, Mathias & Dougherty, 2008) and the effects of puberty are also thought to play a part in influencing selfharming behaviour (Patton, Hemphill, Byers et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Most participants reported that, over time, they had learned to make sense of selfharm and to understand why young people had self-harmed. Many of the reasons they identified are reported in the research literature as factors which are known to contribute to self-harm, including: psychiatric and personality disorders (Hawton, Saunders, Topiwala & Haw, 2013); psychological characteristics such as impulsivity and low self-esteem (Madge et al 2011); stressful life events such as difficulties in relationships, knowing someone else who self-harms or who has attempted suicide, being sexually abused or being bullied (Madge et al 2011;Werbart Törnblom, Werbart & Rydelius, 2015). A high level of impulsivity in early childhood has been implicated in later adolescent self-harming (Goldston, Daniel, Mathias & Dougherty, 2008) and the effects of puberty are also thought to play a part in influencing selfharming behaviour (Patton, Hemphill, Byers et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Mental disorders also increase distress (Eskin et al, ) and substantial impairment in academic performance (Auerbach et al, ). Childhood and adolescent adversities, bullying, stressful life experiences, and personal traits could also be related (Holt et al, ; Johnson et al, ; L. Wang et al, ; Werbart Törnblom, Werbart, & Rydelius, ). On the contrary, positive relationships with peers and family might be STB protective factors (Cash & Bridge, ; Thompson, Eggert, & Herting, ).…”
Section: Introductionmentioning
confidence: 99%
“…Males have higher rates of completed suicide and lower rates of suicide attempt, compared to females. Likewise, males are three‐ to four‐fold more likely to die by suicide than females (Eaton et al, ; Werbart Törnblom et al, ). The association between suicide and masculinity may play a role in creating a genuine gender gap in suicide rates (Canetto & Sakinofsky, ).…”
Section: Introductionmentioning
confidence: 99%
“…Shamefulness and discomfort associated with mental illness and relevant treatment was described as one of young people's greatest concerns in seeking help for suicidal ideation and behaviours ( Curtis, 2010 , Czyz et al, 2013 ), which was echoed by the interviews from the informants of young suicide decedents ( Moskos et al, 2007 , Tornblom et al, 2015 ). Although quantitative studies among the students in Australia, China or US ( Chan et al, 2014 , Yakunina et al, 2010 ) have not found a significant effect of stigma on professional help-seeking intentions using the Stigma of Suicide Scale (SOSS, Batterham et al, 2013 ) or the Stigma of Suicide Scale (SSS, Yakunina et al, 2010 ), stigmatising attitudes towards suicidal individuals may still play an important role in young peoples' professional help-seeking attitudes and intentions, as indicated by the findings in a large community sample ( Calear et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%